Feminist Collections, v.23, no.3 (spring 2002) - (:unkn) unknown (My University, 2002)
Subtitle: A Quarterly of Women's Studies Resources. 44p.
FROM THE EDITORS. BOOK REVIEWS: Young Feminists’ Tales, by Sara N.S. Meirowitz. SPECIAL BOOK REVIEW SECTION: WOMEN IN THE CIVIL RIGHTS MOVEMENT: Introduction, by Christina Greene. Sisterhood of Courage: Women in the Movement, by Deborah Louis. Allies for Freedom: Non-Black Women in the Movement, by Stephen D. Grubman-Black. Biographies of Frances Freeborn Pauley and Fannie Lou Hamer, by Kalí Tal. FEMINIST VISIONS: Feminism and Sex Work: A Review of Four Films, by Catherine M. Orr. WORLD WIDE WEB REVIEW: Internet-Based Resources on Female Genital Mutilation, by Tobe Levin. COMPUTER TALK: Compiled by JoAnne Lehman. NEW REFERENCE WORKS IN WOMEN'S STUDIES: Reviewed by Phyllis Holman Weisbard. PERIODICAL NOTES: Compiled by JoAnne Lehman. ITEMS OF NOTE: Compiled by Caroline Vantine. BOOKS RECENTLY RECEIVED. SUBSCRIPTION FORM.
Keywords: Women's Studies; Gender; Feminism; Library Resources; Reviews; Young Feminists; Videos on Feminism and Sex Work; Female Genital Mutilation; Civil Rights Movement; Fannie Lou Hamer; Frances Freeborn Pauley